The Effect of New Formula (Nut Meg Extract) As A Mouth Wash Compared With Chlorhexidine Mouth Wash - Maha T Al-Saffar; Rafi' A Al-Talib; Ghada A Taqa; Amer A Taqa (University of Mosul, College of Dentistry, 2008)
Aims: To compare the anti-plaque and anti-inflammatory effects of new mouth rinse (nut meg) to the conventional chlorhexidine anti-inflammatory and anti-plaque effects (in vivo study). Materials and Methods: Sixteen dental students in the final year participated in this study (2 females and 14 males) aged 22-23 years (mean 22.5 years). A double blind study was carried out by measuring plaque index, modified gingival index and bleeding index pre-treatment and post-treatment with the two mouth rinses (nut meg and chlorhexidine). The same volunteers were participated in the two test periods and each period lasted 5 days with a wash out twice daily. Deterioration rate for each parameter was derived and used ass a unit of analysis. Results: The new mouth rinse (nut meg extract) had a significant anti-plaque and anti-inflammatory effects (measured by reduction in bleeding index), which was nearly equivalent to the anti-plaque and anti-inflammatory effects of chlorhexidine. No significant difference was noticed between post-treatment group (p > 0.05) of the two mouth rinses regarding plaque and bleeding indices. Conclusion: The nut meg extract mouth rinse had anti-inflammatory effect which encourage its use in dentistry as a new mouth rinse for the treatment of gingivitis.